Translating English Phrasal Verbs Into Indonesian Language - Istima Istima; Yen Polisda (LINGUA LITERA : journal of english linguistics and literature, 2016)
This article reports the types of phrasal verbs and their translated variations into Indonesian language in a novel by Sir Arthur ConanDoyle. It is interesting to study phrasal verbs due to their special meanings. The data were gained form two novels, namely, A Study in Scarlet, the English version and Penelusuran Benang Merah, the Indonesian version. This research was a descriptive qualitative research. The findings of this research showed that the types of phrasal verbs are: transitive, intransitive, separable, and inseparable phrasal verbs. I addition, it was found that there are some variations of translated phrasalverbs in Indonesian language: one-word, two-word, and more than two words.